Reshaping economics to encompass quality of life issues - Ostasiewicz, Katarzyna; Ostasiewicz, Walenty (Silesian Statistical Reviev, 2015)
In this paper we have given a short account of the shortfalls of neoclassical economics, far removed from Aristotelian political economics, which was considered by him as the art of household management. The objective of it was a flourishing life or the Good Life. The main aim of humankind is the development of a desirable way of living and sustaining the quality of life, also for future generations. In order to achieve that goal, people created a number of institutions to facilitate achieving that end. All institutions, as they are devised for human purposes, cannot be outside human control, they should serve society. In the paper it is argued that the economy, as one of the social institutions, should play a particular role in enhancing human and non-human well-being. The paper contains the proposal of a unified system of measuring institutional and eco-system performance. Moreover, it is argued that among many proposals for the development of new proposals for studying economic matters, ecological economics is the most suitable for researching into the quality of life
Śląski Przegląd Statystyczny = Silesian Statistical Review, 2015, Nr 13 (19), s. 137-159
Keywords: quality of life; neoclassical economics; ecological economics; sustainable development; performance measurement; jakość życia; ekonomia neoklasyczna; ekonomia ekologiczna; zrównoważony rozwój; pomiar jakości życia